Connective Tissue and Fibroblast Senescence in Skin Aging - Wlaschek, Meinhard; Maity, Pallab; Makrantonaki, Evgenia; Scharffetter-Kochanek, Karin (Journal of investigative dermatology, 2021)
There is increasing evidence that skin aging is significantly enforced by the accumulation of senescent dermal fibroblasts. Various stressors damaging macromolecules inside and outside fibroblasts are responsible. In addition, NK cells fail to adequately remove senescent (SEN) fibroblasts from tissues. SEN fibroblasts by the release of the proinflammatory, tissue degrading senescent-associated secretory phenotype factors and vesicles with distinct cargo impact on their endogenous niche and spread senescence and skin aging. In this review, we will further discuss less noticed facets, including the plasticity of distinct dermal fibroblast phenotypes, the underestimated impact of the extracellular matrix itself, and the depletion of fibroblast subsets on skin homeostasis and aging.